Power and responsibility in planning adult education programs - Ronald . M Cervero; Arthur L. Wilson (Adult Education Research Conference, 1993)
The paper offers adult educators a practical guide to normatively explicit planning practice by taking power and interests as central to action and explaining what adult educators can do to plan programs responsibly.